Edema worsens target coverage in high-dose-rate interstitial brachytherapy of mobile tongue cancer: a report of two cases - Yoshida, Ken; Yamazaki, Hideya; Kotsuma, Tadayuki; Akiyama, Hironori; Takenaka, Tadashi; Masui, Koji; Yoshioka, Yasuo; Uesugi, Yasuo; Shimbo, Taiju; Yoshikawa, Nobuhiko; Yoshioka, Hiroto; Arika, Takumi; et al. (Journal of Contemporary Brachytherapy, 2017)
Purpose : We report our study on two patients to highlight the risk of underdosage of the clinical target volume (CTV) due to edema during high-dose-rate interstitial brachytherapy (HDR-ISBT) of mobile tongue cancer. Material and methods : To treat the lateral side of the CTV, flexible applicator tubes were implanted on the mouth floor. Two-dimensional planning was performed using X-ray images for Case 1, and three-dimensional (3D) planning was performed using computed tomography (CT) for Case 2. Prescribed doses for both cases were 54 Gy in nine fractions. Case reports : Case 1 was treated for cancer of the right lateral border of the tongue in 2005. Tongue edema occurred after implantation, and part of the lateral border of the tongue protruded between the applicator tubes. Acute mucosal reaction abated in the protruded area earlier than in the other parts of the CTV. In this case, the tumor recurred in this area 5 months after the treatment. Case 2 was treated for cancer of the left lateral border of the tongue. Because tongue edema occurred in this case also, plastic splints were inserted between the applicator tubes to push the edematous region into the irradiated area. The mucosal surface of the CTV was covered by the 70% isodose, and 100% isodose line for before and after splint insertion. Local control of the tumor was achieved 4 years after treatment. Discussion and conclusions : To ensure sufficient target coverage, 3D image-based planning using CT should be performed, followed by re-planning using repeated CT as needed. Also, the development of devices to prevent protrusion of the edematous tissue outside the target area will help to ensure the full dosing of CTV.